The Graduated Embryo Score of Embryos from Infertile Women with and without Peritoneal Endometriosis - Juliana Caran; Vanessa Krebs Genro; Carlos Augusto Bastos de Souza; João Sabino Cunha-Filho
Abstract Objective To determine embryo quality (mean graduated embryo score [GES]) in infertile patients with endometriosis undergoing in vitro fertilization with embryo transfer (IVF-ET) compared with infertile patients without endometriosis. Methods A case-control study was performed comparing 706 embryos (162 patients) divided into 2 groups: 472 embryos derived from patients without endometriosis (n= 109, infertile patients with tubal infertility) and 234 embryos from patients in the study group (n= 53, infertile patients with peritoneal endometriosis). All patients were subjected to IVF using an oestradiol-antagonist-recombinant follicle-stimulating hormone (FSH) protocol for ovarian stimulation. Themean GESwas performed to evaluate all embryos at 3 points in time: 16 to 18 hours, 25 to 27 hours, and 64 to 67 hours. Embryo evaluation was performed according to the following parameters: fragmentation, nucleolar alignment, polar body apposition, blastomere number/morphology, and symmetry. The primary outcomemeasure was the mean GES score.We also compared fertilization, implantation, and pregnancy rates. Results Although the number of embryos transferred was greater in patients with endometriosis than in the control group (2.38 ± 0.66 versus 2.15 ± 0.54; p= 0.001), the meanGESwas similar inbothgroups (71 ± 19.8 versus 71.9 ± 23.5; p= 0.881). Likewise, the fertilization ratewas similar in all groups, being 61% in patients with endometriosis and 59% in the control group (p= 0.511). No significant differences were observed in the implantation (21% versus 22%; [p= 0.989]) and pregnancy rates (26.4% versus 28.4%; p= 0.989). Conclusion Embryo quality measured by the mean GES was not influenced by peritoneal endometriosis. Likewise, the evaluated reproductive outcomes were similar between infertile patients with and without endometriosis.